ARTIFICAL INTELLIGENCE IN EDUCATION: SYSTEMATIC REVIEW OF LITERATURE - Zhaidakbayeva, Л.Қ.; Тynyshbek, Қ,Қ. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The introduction of artificial intelligence (hereinafter referred to as AI) into education (Artificial Intelligence in Education, hereinafter referred to as AIED) has become a significant field of research, covering many perspectives. This article is a literature review based on a bibliometric analysis of 1463 research papers and a content (content) analysis of 118 selected articles. The review addresses the following key issues: the main categories of AI applications in education, priority research topics and their results, and methodological aspects of research. The analysis highlights a wide range of AI applications, including adaptive learning, personalized learning, intelligent assessment and Management, Profiling and forecasting, and its new products. Research topics focus more deeply on the technical design of educational systems, as well as the study of implementation, impact, and issues of AIED. The review also highlights the diversity of theories used in AIED research, the multidisciplinary nature of publications, and insufficiently studied areas. This work will provide valuable information for researchers seeking to understand the current state of AIED research and identify future opportunities in this dynamic area.